2016
DOI: 10.1002/micr.30082
|View full text |Cite
|
Sign up to set email alerts
|

Critical time for neovascularization/angiogenesis to allow free flap survival after delayed postoperative anastomotic compromise without surgical intervention: A review of the literature

Abstract: This analysis suggests that free flaps compromised by vascular thrombosis or pedicle ligation may survive with only conservative therapy when the event occurs after a minimal critical time period. Flap survival is more probable when arterial occlusion or pedicle ligation occurs after postoperative day 12, but this minimal critical period may be as low as 6 days for arterial occlusion. © 2016 Wiley Periodicals, Inc. Microsurgery 36:604-612, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 44 publications
1
39
0
2
Order By: Relevance
“…However, at least one study has shown that the minimal critical period for flap survival for arterial occlusion is six days. 21 Therefore, we believe that a barrier would not have affected the tissue viability and thereby the visual appearance of the flap three days after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…However, at least one study has shown that the minimal critical period for flap survival for arterial occlusion is six days. 21 Therefore, we believe that a barrier would not have affected the tissue viability and thereby the visual appearance of the flap three days after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, Jones, Kuzon, Shestak, and Roth () also presented a case of a disrupted jejunal pedicle on the 12th postoperative day and survival of the flap. Yoon & Jones () reviewed the literature and concluded that a longer postoperative period before ligation or obstruction of the pedicle is required for jejunal flap survival. However, these reports did not recommend subtotal liberation of the flap from the surrounding tissues, but they only indicated pedicle transection.…”
Section: Discussionmentioning
confidence: 99%
“…also presented a case of a disrupted jejunal pedicle on the 12th postoperative day and survival of the flap Yoon & Jones (2016). reviewed the literature and concluded that a longer postoperative period before ligation or obstruction of the pedicle is required for jejunal flap survival.…”
mentioning
confidence: 98%
“…A study in a swine model has shown that neovascularization between the flap and the surrounding tissue becomes well established by the 8th day after free tissue transfer (Black, Chait, O'Brien, Sykes, & Sharzer, ) and serves as the basis for the staged inset principle. A clinical study determined that free flaps are able to survive a pedicle occlusion only after postoperative day 10 (Granzow, Li, Caton, & Boyd, ; Yoon & Jones, ) Another case series that investigated the effect of early pedicle loss documented that 50% of their flaps were able to survive completely after the loss of arterial inflow on the postoperative day 7 (Salgado et al, ) However, considering the complexity of head and neck procedures and confounding risk factors such as preoperative radiotherapy and scarring of the recipient site tissue bed, a period of 3–4 weeks is preferred. An advantage of the staged flap inset is the much shorter and simpler operation of the second procedure.…”
Section: Discussionmentioning
confidence: 99%